Validation of the short form Compulsive Internet Use Scale in Students - Hassan Mahmoudian; abbas taghizade; Samira Golmirzaie (مطالعات روانشناسی تربیتی)
The present study aimed to determine the psychometric properties of the short form of the Compulsive Internet Use Scale developed by Gmel et al. (2019) among students in Tehran.Methods: This transcultural adaptation and psychometric study was carried out on 760 students from Tehran during the academic year 2021-2022, selected through convenience sampling, with 712 questionnaires deemed analyzable. the Compulsive Internet Use Scale developed by Gmel et al. (2019) comprising 8 self-report items employed. The psychometric characteristics including face, content, and construct validities, along with reliability, were appraised using SPSS and Lisrel software.Findings: The findings indicated that the Compulsive Internet Use Scale has acceptable face and content validity. The results of the exploratory factor analysis using principal component analysis extracted five factors, labeled as loss of control, preoccupation, conflict, coping, and withdrawal symptoms, which accounted for 52.139% of the total variance. The results of the confirmatory factor analysis demonstrated that the structure of the scale has an acceptable fit with the data, as all goodness-of-fit indices support the model: (χ²/df = 2.61 <3), RMSEA = 0.070, GFI = 0.91, RMR = 0.04, NFI = 0.86, CFI = 0.91. Reliability results showed that the overall Cronbach's alpha coefficient was 0/94, and the intra-class correlation coefficient and Pearson correlation coefficient for test-retest reliability were 0.78 and 0.77, respectively.Conclusion: According to the findings of this study, it can be stated that the short form of the Compulsive Internet Use Scale by Gmel et al. (2019) possesses good psychometric properties.